Skills, expertise and role of Australian emergency clinicians in caring for people with advanced cancer. Issue 1 (9th January 2015) - Jelinek, G A; Marck, C H; Weil, J; Lane, H; Philip, J; Boughey, M; Weiland, T J
Abstract : Objectives: To explore the views of Australian emergency department (ED) clinicians about their skills, role and expertise in caring for people with advanced cancer. Methods: A cross-sectional electronic survey of doctors and nurses working in Australian EDs was undertaken. Comparisons were made by demographics and whether respondents had received palliative care education. Results: The sample comprised 444 doctors (response rate 13.5%), the majority Fellows (emergency medicine specialists) of the Australasian College for Emergency Medicine, and 237 nurses, from all states, territories and regions (metropolitan and regional). A minority (n=123, 20.6%) felt that the ED was not an appropriate place for patients with advanced cancer to present for acute care, while almost two-thirds (n=397, 64.8%) found caring for such patients rewarding, particularly nurses and those who had received palliative care education; very few (n=40, 6.5%) reported feeling uncomfortable talking to the families of dying patients. A minority (n=129, 21.0%) felt that it was not appropriate for junior medical staff to assess these patients, nurses much more than doctors (42.9% vs 8.5%, p<0.001). Over half (n=338, 55.1%) felt sufficiently skilled in managing pain for people with advanced cancer, with Fellows, more experienced doctors, and those who had received palliative care education more likely to feel skilled. Conclusions: ED clinicians in Australia, particularly those who have received palliative care education, feel comfortable and adequately skilled in managing people with advanced cancer presenting to EDs, and most find it rewarding. The importance of palliative care education to emergency clinicians' training should be recognised.